Designing of Device for Endoscopic Surgery In Experimental Animals - Grebenyuk, A.I.; Чиж, М.О.; Byzov, D.V.; Rohoza, L.A.; Antonenko, E.A.; Lukyanenko, P.G.; Sandomirsky, B.P. (Problems of Cryobiology and Cryomedicine, 26(2), 189. https://doi.org/10.15407/cryo26.02.189, 2016)
Designing of Device for Endoscopic Surgery In Experimental Animals
Разработка установки для эндоскопических операций на экспериментальных животных
Grebenyuk, A.I., Chizh, N.A., Byzov, D.V., Rohoza, L.A., Antonenko, E.A., Lukyanenko, P.G., Sandomirsky, B.P. (2016). Designing of Device for Endoscopic Surgery In Experimental Animals. Problems of Cryobiology and Cryomedicine, 26(2), 189. https://doi.org/10.15407/cryo26.02.189
Keywords: Device for Endoscopic Surgery; Experimental Animals